SISTEM PENUNJANG KEPUTUSAN PEMILIHAN KARYAWAN BERPRESTASI DENGAN METODE ANALITICAL HIERARCHY PROCESS (AHP) PADA PT. ICHIYA INDONESIA - Dian Septiani; Fernando B. Siahaan (JURNAL TEKNIK KOMPUTER AMIK BSI, 2017)
This research aims to build decision support system that have the ability to analyze in the selection of imployes is doing by using AHP method. Employees can be compared to each other from the assessment factors and alternative so as to provide an output value for the intensity of the priorities in generating system that provide an assessment on each employee.It is usefull to make it esier for decision makers that are related to the issue of the election of the employee is doing. Decision support information system (including knowledge-based system (knowledge management) Expert choice is the solution for decision making in the company.For the sake of the efficiency an effectiveness of work then the right decision-making is indispensable in system that has the ability to analyze the election employess perfume.Keywords: Decision support system, selection of imployes, Expert Choice